PENGARUH KOMPRES HANGAT TERHADAP PENURUNAN NYERI PUNGGUNG PADA KEHAMILAN TRIMESTER III DI NAGARI KOTO PADANG WILAYAH KERJA PUKESMAS KOTO BARU - Evin Noviana Sari; Rati Purwati; Rina Hayu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
West Sumatra has 121,161 pregnant women. In Nagari Koto Padang (the working area of the Koto Baru Health Center), based on an initial survey on December 18, 2024, of 4 pregnant women in their third trimester, 3 experienced moderate back pain, and 1 did not experience back pain. Treatment of back pain in pregnant women can be done with non-pharmacological therapy, one of which is with warm compresses. The purpose of this study was to determine the effect of giving warm compresses on reducing back pain in the third trimester of pregnancy in Nagari Koto Padang, the working area of the Koto Baru Health Center. his type of research uses a quantitative approach with a pre-experimental design with a research design using one group pre-test post-test. This research was conducted in May 2025. The population of this study were third-trimester pregnant women who experienced back pain in Nagari Koto Padang, the working area of the Koto Baru Health Center with a sample of 10 people. Data processing was editing, coding, scoring and tabulating. Univariate analysis used the mean, standard deviation and bivariate analysis used the paired T-test. The results showed that before the intervention, 50% of respondents experienced mild pain and 50% moderate pain. After being given a warm compress, 70% did not experience pain, and 30% experienced mild pain. Statistical tests showed a p-value = 0.01, which means there was a significant effect of giving warm compresses on reducing back pain. Through the leadership of the Kuranji Community Health Center, the provision of warm compresses can be included in the Community Health Center program as a non-pharmacological treatment that can provide a positive effect in reducing back pain in the third trimester of pregnancy